2012
DOI: 10.1097/hp.0b013e3182666d6f
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hematopoietic Stem Cell Damage in a Murine Model of the Hematopoietic Syndrome of the Acute Radiation Syndrome

Abstract: Residual bone marrow damage (RBMD) persists for years following exposure to radiation and is believed to be due to decreased self-renewal potential of radiation-damaged hematopoietic stem cells (HSC). Current literature has examined primarily sub-lethal doses of radiation and time points within a few months of exposure. In this study, we examined RBMD in mice surviving lethal doses of total body ionizing irradiation (TBI) in a murine model of the Hematopoietic Syndrome of the Acute Radiation Syndrome (H-ARS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
79
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 55 publications
18
79
1
Order By: Relevance
“…BM cells from irradiated mice exhibit a persistent engraftment defect postirradiation, 24,25 whereas those from mice treated with 5-FU engraft successfully. 26 Expression of CD166 on LSK from sublethally irradiated mice was significantly reduced ( Figure 4F).…”
Section: Stress Response and Homing Of Hematopoietic Cells From Cd166mentioning
confidence: 99%
“…BM cells from irradiated mice exhibit a persistent engraftment defect postirradiation, 24,25 whereas those from mice treated with 5-FU engraft successfully. 26 Expression of CD166 on LSK from sublethally irradiated mice was significantly reduced ( Figure 4F).…”
Section: Stress Response and Homing Of Hematopoietic Cells From Cd166mentioning
confidence: 99%
“…The hematopoietic system is highly sensitive to IR, and in particular, IR doses beyond 2 Gy can lead to myelosuppression that is characterized by neutropenia, lymphocytopenia, and thrombocytopenia. Collectively, hematopoietic acute radiation syndrome (H-ARS) increases the risk of infection, bleeding, and death (1)(2)(3)(4)(5)(6)(7)(8)(9). There is an unmet need for effective interventions to mitigate the progression of H-ARS after IR exposure (10).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of animals to ionizing radiation can induce long-term hematopoietic cells damage, which is mainly the self-renewal damage for hematopoietic stem cells (HSCs) (Chua et al, 2012). Wang et al (2006) found C57BL/6 mice exposed to a sub-lethal dose of gamma irradiation induced a persistent reduction in LKS+ HSCs.…”
Section: Discussionmentioning
confidence: 99%